Study of terrestrial isopods (Crustacea: Isopoda: Oniscidea) in three localities of Boyaca, Colombia - Preciado, Ariel Fernando; Martínez, Jhon Wilson (Revista de Ciencias Agrícolas, 2015)
The composition and abundance of terrestrial isopods were analyzed by direct collection at three localities in the department of Boyacá, Colombia: Tinjacá, Tibasosa, and Tota. Five species distributed in two families were identified from a total of 2516 field collected individuals, for which new occurrence reports in Boyacá are presented for:Porcellio dilatatus (Brandt), Porcellionides pruinosus (Brandt), Armadillidium vulgare (Latreille) and Armadillidium nasatum (Budde-Lund). Statistically significant differences were found regarding the number of individuals, locality, and species present. The greatest abundance and richness were found in the municipality of Tibasosa. The isopods sampled were mainly found in the so-called ‘plateo’ microhabitat, or the surrounding soil of the vegetation. The most abundant species was P. scaber and the most common one was A. vulgare. The environmental conditions were not related to the number of individuals collected.